Syndicate Group Learning Instruction: An Interactive Way to Improve Students’ Activities and Learning Outcomes - Armansyah, Armansyah; Azmi, Irham; Kalean, Arman (LITPAM, 2022)
This research aims to describe the influence of Syndicate Group Learning Instruction on the improvement of activities and physics learning outcomes of 8th-grade students at SMPN 18 Mataram. The research design employed is an experimental study. The population of this study comprises all 8th-grade students at SMPN 18 Mataram. The sample consists of 22 students from class VIIIA as the experimental group and 24 students from class VIIIC as the control group selected using a random sampling technique. Data for this study were obtained through pre-tests and post-tests given to the sample class students. Data collection techniques involve using observation sheets and formative tests that have been validated for validity, reliability, differential power, and difficulty index. Based on the data analysis, the average pre-test score for the experimental group is 56.13; for the control group, it is 46.66, categorized as homogeneous and normally distributed. The post-test results show an average of 69.31 for the experimental group and 58.54 for the control group. The final test data of the sample class students were analyzed using the t-test, resulting in a calculated t-value of 2.160 and a tabulated t-value of 2.016. The calculated t-value is greater than the tabulated t-value at a 5% error level, thus rejecting the null hypothesis (Ho). It can be concluded that the use of Syndicate Group Learning Instruction has a significant influence on the activities and physics learning outcomes of 8th-grade students at SMPN 18 Mataram.